2022
DOI: 10.3390/metabo12020148
|View full text |Cite
|
Sign up to set email alerts
|

Fecal 1H-NMR Metabolomics: A Comparison of Sample Preparation Methods for NMR and Novel in Silico Baseline Correction

Abstract: Analysis of enteric microbiota function indirectly through the fecal metabolome has the potential to be an informative diagnostic tool. However, metabolomic analysis of feces is hampered by high concentrations of macromolecules such as proteins, fats, and fiber in samples. Three methods—ultrafiltration (UF), Bligh–Dyer (BD), and no extraction (samples added directly to buffer, vortexed, and centrifuged)—were tested on multiple rat (n = 10) and chicken (n = 8) fecal samples to ascertain whether the methods work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…One potential limitation of the BD extraction method is the occurrence of baseline distortions due to the incomplete removal of macromolecules in samples that are high in proteins, fats, and/or fiber such as feces ( Brown et al., 2022 ). We did not observe substantive baseline distortions for feather pulp samples extracted with the BD method.…”
Section: Resultsmentioning
confidence: 99%
“…One potential limitation of the BD extraction method is the occurrence of baseline distortions due to the incomplete removal of macromolecules in samples that are high in proteins, fats, and/or fiber such as feces ( Brown et al., 2022 ). We did not observe substantive baseline distortions for feather pulp samples extracted with the BD method.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolite spectra were obtained using the 1-D NOESY gradient pulse pre-saturation water suppression pulse sequence ‘noesygppr1d’ with 10 ms mixing time as previously described [ 30 ]. Briefly, each sample was run for 512 scans to a total acquisition size of 128 k, a spectral window of 20.5 ppm, a total data acquisition time of 4.56 s, a transmitter offset of ≈4.7 ppm, and a recycle delay of 1 s (total T1 relaxation recovery time of 5.56 s).…”
Section: Methodsmentioning
confidence: 99%
“…Although there are many potential means of assessing stress, metabolomics has shown promise as a highly sensitive method of determining a stress condition based on relative concentrations of metabolites in biological samples [ 24 ]. In fact, recent nuclear magnetic resonance (NMR) spectroscopy-based metabolomics studies have shown that the metabolomes of eggs, breast muscle, liver, kidney, feces, and feathers can be used in a variety of ways to better understand domestic poultry physiology, including stress [ 6 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. However, the use of metabolomics to identify biomarkers of health in poultry remains in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…This can be performed experimentally 21 or with computational methods. 22 , 23 However, we advocate the use of SMolESY, because of its ease of application to 1 H NMR spectra (including retrospective application where proteinuria is observed after the fact), being fast and highly effective method for removing broad baseline signals from protein and improving the estimation of normalization coefficients. Our observations and proposed methodology are of high importance for the accurate normalization of urine biofluid 1 H NMR spectra, especially in the context of studies on diseases and phenotypes where proteinuria is likely to be present (e.g., diabetes, chronic kidney disease, pregnancy, infection, or protein rich diet).…”
mentioning
confidence: 99%
“…We recommend the removal of protein baseline signals prior to estimation of normalization coefficients. This can be performed experimentally or with computational methods. , However, we advocate the use of SMolESY, because of its ease of application to 1 H NMR spectra (including retrospective application where proteinuria is observed after the fact), being fast and highly effective method for removing broad baseline signals from protein and improving the estimation of normalization coefficients. Our observations and proposed methodology are of high importance for the accurate normalization of urine biofluid 1 H NMR spectra, especially in the context of studies on diseases and phenotypes where proteinuria is likely to be present (e.g., diabetes, chronic kidney disease, pregnancy, infection, or protein rich diet)…”
mentioning
confidence: 99%